Kdo smo Ilustrirana zgodovina slovenstva - Pleterski, Andrej (ZRC SAZU, Založba ZRC, 2020)
Simply put, the modern Slovenian nation began as a cultural project in the age of Enlightenment. Its basic axis has been Standard Slovenian as one of Slavic languages. The book describes from where the speakers of the initial common Slavic language arrived at our place, as well as where and when Slavs came into being. Throughout the history of long ages the author observes the relationship between the speakers of the language, political power, and particularly the Church as an institution with a universal ideology which as such does not in any way encourage local identity. The book also recalls the millennial roots of Slovenian identity whose present state is not a logical consequence of the past, much less the beginning of self-evident future. The author knows that the final image of the past is always created by the reader themself, therefore using challenging illustrations he constantly encourages them to think. The author also does not expect the reader to agree with him, but would like them to find some causal connections of their own and thus recover the lost memory of who they are.